2008
DOI: 10.1172/jci33522
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ– and TNF-dependent bystander eradication of antigen-loss variants in established mouse cancers

Abstract: Tumors elicit antitumor immune responses, but over time they evolve and can escape immune control through various mechanisms, including the loss of the antigen to which the response is directed. The escape of antigenloss variants (ALVs) is a major obstacle to T cell-based immunotherapy for cancer. However, cancers can be cured if both the number of CTLs and the expression of antigen are high enough to allow targeting of not only tumor cells, but also the tumor stroma. Here, we showed that IFN-γ and TNF produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
147
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(160 citation statements)
references
References 57 publications
12
147
0
1
Order By: Relevance
“…changes in macrophages in the tumour environment. These data are consistent with the results of Zhang et al, 46 who demonstrated that effector T cells caused tumour destruction by targeting the non-malignant cells in the tumour stroma. We show that aOX40 therapy led to a decrease in the proportion of macrophages in the tumour, and further experiments will be necessary to distinguish whether this process occurs through selective macrophage destruction by effector T cells, macrophage differentiation within the tumour, or recruitment of new macrophages to the altered tumour site.…”
Section: Discussionsupporting
confidence: 93%
“…changes in macrophages in the tumour environment. These data are consistent with the results of Zhang et al, 46 who demonstrated that effector T cells caused tumour destruction by targeting the non-malignant cells in the tumour stroma. We show that aOX40 therapy led to a decrease in the proportion of macrophages in the tumour, and further experiments will be necessary to distinguish whether this process occurs through selective macrophage destruction by effector T cells, macrophage differentiation within the tumour, or recruitment of new macrophages to the altered tumour site.…”
Section: Discussionsupporting
confidence: 93%
“…It is clear from mouse models that adoptively transferred antigen-specific T cells are capable of eradicating established cancer (6)(7)(8), and the ability of CTLs to directly kill tumor and/or stromal cells is thought to be important for tumor elimination (9)(10)(11). Nonetheless, cytokines such as IFNg and TNFa produced by T cells are also likely to contribute to the prevention of tumor growth by ACT via mechanisms other than cell lysis (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…29 Also, the cytokines secreted by Th1 T cells can target the tumor environment and eliminate antigen-loss tumor variants. [30][31][32] Finally, tumor antigen-specific Th1 T cells can also directly target tumor cells through cytotoxicity, FASL, or senescence induction. [33][34][35][36] Therefore, the percentage of Th1 CD4 C T cells in the stromal environment is directly correlated with a cancer patient's prognosis.…”
Section: E1232220-12mentioning
confidence: 99%